APPLICATION OF GEOSYNTHETIC MATERIALS IN CANAL LINING: EFFICIENCY, DURABILITY, AND ENVIRONMENTAL BENEFITS - Sh. Egamberdiyeva (Bright Mind Publishing, 2025)
This research article investigates the application of geosynthetic materials in canal lining, focusing on their efficiency, durability, and environmental benefits. As water scarcity intensifies globally, the need for efficient water management systems in arid and semi-arid regions becomes more critical. One of the major sources of water loss in irrigation and conveyance systems is seepage through unlined or poorly lined canals. Geosynthetics—synthetic polymeric materials such as geomembranes, geotextiles, geogrids, and geocomposites—offer a modern, cost-effective, and environmentally sustainable solution to reduce seepage and increase the operational lifespan of canal systems. The study synthesizes a multidisciplinary review of hydraulic performance data, material properties, installation techniques, field performance metrics, and environmental impact assessments. A comparative analysis of conventional lining materials (e.g., concrete, compacted clay) with geosynthetics underlines the technological advancements and practical implications of adopting geosynthetics in large-scale water management infrastructures. The paper also discusses regional case studies, especially in Central Asia, with specific attention to the challenges and opportunities in Uzbekistan. The findings suggest that geosynthetic-lined canals demonstrate superior hydraulic efficiency, prolonged durability, and reduced ecological footprint compared to traditional methods. The study provides actionable recommendations for engineers, policymakers, and environmental planners aiming to modernize irrigation infrastructure and promote sustainable water use practices.
Keywords: Geosynthetics, canal lining, seepage control, hydraulic efficiency, durability, environmental impact, irrigation infrastructure.